2011
DOI: 10.1093/jscr/2011.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal duplication with simultaneous acute appendicitis and appendicular perforation causing small bowel obstruction

Abstract: Acute appendicitis, as well as intestinal obstruction, is a common surgical emergencies. Both the conditions can present as an acute abdomen, however the diagnosis of acute appendicitis can be overlooked when it presents as a small bowel obstruction. Difficulties in correctly identifying the cause of pain can be hazardous to the patient and care needs to be taken in obtaining a prompt and accurate diagnosis enabling the most appropriate management. Appendiceal duplication although rare and difficult to diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…Peritoneal adhesions, which were found in up to 95% of patients after intra‐abdominal surgery, are the leading cause of SBOs 10,19–21 . When it comes to appendicitis, previous studies reported the rate of adhesive SBO after LA to be 1.4% 22–24 . In our study, 16 cases were included in the SBO group.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Peritoneal adhesions, which were found in up to 95% of patients after intra‐abdominal surgery, are the leading cause of SBOs 10,19–21 . When it comes to appendicitis, previous studies reported the rate of adhesive SBO after LA to be 1.4% 22–24 . In our study, 16 cases were included in the SBO group.…”
Section: Discussionmentioning
confidence: 74%
“…10,[19][20][21] When it comes to appendicitis, previous studies reported the rate of adhesive SBO after LA to be 1.4%. [22][23][24] In our study, 16 cases were included in the SBO group. Standard conservative management was successful in 14 patients, and operative therapy was recommended for those who failed conservative therapy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several classifications have been described to classify a double appendix. The most commonly used is the Cave–Wallbridge classification [4] . These classification are A, B1, B2 and C. However this has been updated to include other subtypes like the horseshoe appendix and triplet appendix [4] , [5] (see Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used is the Cave–Wallbridge classification [4] . These classification are A, B1, B2 and C. However this has been updated to include other subtypes like the horseshoe appendix and triplet appendix [4] , [5] (see Table 1 ). The diagnosis can either be an incidental finding on imaging or through complicated presentations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation